Soliton pulse generation using a swcntspolyvinyl alcohol thin film based passive saturable absorber - Ahmad, F.; Harun, Sulaiman Wadi; Nor, Roslan Md; Ahmad, Harith; Ibrahim, M.H. (Asian Research Publishing Network, 2016)
Fabrication of single-walled carbon nanotubes (SWCNTs) polymer composite based thin film passive saturable absorber was demonstrated using a simple solution casting approach. The fabricated thin film is integrated in erbium-doped fiber laser (EDFL) in ring cavity and generate soliton pulsed laser. The performance of the generated pulsed laser was recorded with the central wavelength of the self-started stable soliton pulses spectrum at 1556 nm with 4 nm of 3 dB bandwidth and the calculated time-bandwidth product (TBP) is around 0.350. The soliton pulse starts to lase at pump power threshold of 125 mW with a repetition rate, pulse width, average output power, pulse energy, peak power and signal to noise ratio of 15.15 MHz, 710 fs, 0.031 mW, 2.05 pJ, 2.72 W and 50 dB, respectively.